The Effect of Gamified Flipped Classroom on the Improvement of Vocabulary Learning of Iranian Pre-Intermediate EFL Learners - Farhad Fahandezh; Asieyeh Mohammadi (Vision: Journal for Language and Foreign Language Learning, 2021)
The current study aimed to improve vocabulary learning by using gamification in the flipped classroom context. To this end, all of the study’s population comprised high school learners at two high schools in Roodan, a city in Hormozgan, Iran. The participants were divided into three classes, class A consisting of 40 students, class B comprising 40 students, and class C consisting of thirty learners. All learners were female. In order to ensure that the learners were homogeneous, the Preliminary English Test (PET) was applied. Class A was chosen as the experimental group (gamified flipped classroom), whereas classes B and C were chosen as the control groups. Data were collected through the vocabulary and placement tests. Results indicate that gamification in the flipped context could have a significant effect on vocabulary improvement. This study suggests certain implications for English teachers, policymakers, and material developers. As a new teaching model, it offers a new method of vocabulary teaching.